The TSN1 Binding Protein RH31 Is a Component of Stress Granules and Participates in Regulation of Salt-Stress Tolerance in Arabidopsis - Liu, Yanan; Liu, Shijie; Shi, Huiying; Ma, Jingyue; Jing, Meng; Han, Yuzhen (Frontiers in Plant Science, 2021)
Tudor staphylococcal nucleases (TSNs) are evolutionarily conserved RNA binding proteins, which include redundant TSN1 and TSN2 in Arabidopsis. It has been showed TSNs are the components of stress granules (SGs) and regulate plant growth under salt stress. In this study, we find a binding protein of TSN1, RH31, which is a DEAD-box RNA helicase (RH). Subcellular localization studies show that RH31 is mainly located in the nucleus, but under salinity, it translocates to the cytoplasm where it accumulates in cytoplasmic granules. After cycloheximide (CHX) treatment which can block the formation of SGs by interfering with mRNP homeostasis, these cytoplasmic granules disappeared. More importantly, RH31 co-localizes with SGs marker protein RBP47. RH31 deletion results in salt-hypersensitive phenotype, while RH31 overexpression causes more resistant to salt stress. In summary, we demonstrate that RH31, the TSN1 binding protein, is a component of plant SGs and participates in regulation of salt-stress tolerance in Arabidopsis.